INFLUENCES OF KNOWLEDGE AND TECHNOLOGY ON STUDENT INVESTMENT INTERESTS: A STRUCTURAL EQUATION MODELING APPROACH - Fadilah, Risa Asti Nur; Dadang, Dadang; Ridwan, Rizky; Riswandi, Dede; Astuti, Dewi Ratnasari (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This empirical research at Universitas Cipasung Tasikmalaya explores the impact of investment motivation, foundational investment knowledge, and technological advancement on student investment interest, a critical component in the evolving economic landscape. The primary goal is to analyze how each factor influences students' inclinations toward the capital market, which is increasingly relevant in the modern economic framework. The study sampled 100 students from the Faculty of Economics & Business, surveyed through an online questionnaire during the 2022-2023 academic year. Data were analyzed using a quantitative approach with Structural Equation Modeling (SEM) processed via the SMART PLS application. The findings carry critical educational implications, underscoring the urgent need to integrate comprehensive investment principles and technology-based frameworks into curricula to develop financially literate students. This study serves as an indispensable blueprint for educational institutions and policymakers to design strategies that align with digital market trends, fostering a generation skilled in the digital financial environment. The research provides insights into key factors affecting student investment interest: although investment motivation did not show a significant positive impact, both basic investment knowledge and technological progress significantly enhanced student investment interest. This highlights the importance of educational strategies focused on basic investment literacy and the integration of advanced technology to cultivate more investment-savvy students.